Sex differences in blood pressure, free radicals and plasma cholesterol fractions in Ren-2 transgenic rats of various ages - Rauchová, H; Hojná, S; Kadlecová, M; Vaněčková, I; Chao, Y M; Chan, Jyh; Zicha, J (Physiological research, 2023)
Sex-related cardiovascular differences were observed in humans as well as in experimental animals. Our previous study demonstrated a marked sexual dimorphism in blood pressure (BP) of 9-month-old heterozygous transgenic Ren 2 rats (TGR), in which mouse Ren-2 renin gene was inserted into the genome of normotensive Hannover Sprague-Dawley rats (HanSD). We found significantly elevated BP only in male TGR, whereas BP of TGR females was similar to that of HanSD females. The aim of our present study was to compare BP of 3- and 6-month-old heterozygous TGR with age- and sex-matched HanSD under the same conditions as we measured in 9-month-old rats. We also monitored the amount of oxidative stress marker, thiobarbituric acid-reactive substances (TBARS), and a main intracellular antioxidant, reduced glutathione in the heart, kidneys and liver. We also measured plasma triglycerides and cholesterol levels. We found an increased mean arterial pressure in both female and male 3-month-old TGR (172±17 vs. 187±4 mm Hg, respectively) compared to HanSD (115±5 vs. 133±3 mm Hg, respectively) but there was a marked sexual dimorphism of 6 month-old TGR where only males were hypertensive (145±5 mm Hg) while females became normotensive (123±7 mm Hg). We did not find any relationship between BP values and concentrations of TBARS or glutathione or plasma lipid levels. Our results demonstrated that 6-month-old TGR exhibited a marked sexual BP dimorphism, which was not dependent on the abnormalities in oxidative stress or cholesterol metabolism.
Keywords: Sex Factors; Cholesterol; cholesterol; renin; Thiobarbituric Acid Reactive Substances; volné radikály; potkani transgenní; Hypertension; ledviny; Female; Kidney; krysa rodu Rattus; zvířata; Free Radicals; Rats, Transgenic; Glutathione; sexuální faktory; Renin; potkani Sprague-Dawley; ženské pohlaví; krevní tlak; Male; hypertenze; glutathion; Rats; Rats, Sprague-Dawley; Animals; mužské pohlaví; Blood Pressure; látky reagující s kyselinou thiobarbiturovou